Perbedaan Kewenangan Dan Syarat Tata Cara Pengangkatan Antara Notaris Dan Notaris Pengganti - Estikharisma Harnum (Jurnal Akta, 2017)
ABSTRACT Notary is a public official authorized to make an authentic deed and has other authorities as referred to in this Act or under any other law. Notary of the Substitute is a person temporarily appointed as a Notary to replace a Notary who is on leave, sick, or temporarily unable to perform his / her position as a Notary as referred to in the UUJN. To become a Notary substitute is required to meet the requirements of appointment procedures that have been specified in the UUJN and in the Minister of Law and Human Rights of the Republic of Indonesia. The problem is there are differences in terms of procedure of appointment between Notary and Notary substitute. The replacement notary has the same authority as the Notary. In performing his duties as a Notary and Notary Substitute, please note the authority to prevent abuse of authority. The writing of this journal aims to know and analyze the differences of authority and terms of procedure of appointment between Notary and Notary replacement. In an effort to know the difference of authority between Notary and Notary Substitute, the author uses the theory of authority with literature method review books against books related to the theme of the journal that I created and sourced from several journals from the internet. The importance of knowing the difference of authority between the Notary and the Notary in lieu of any misuse of authority. The importance of knowing the terms of procedure of appointment between Notary and Notary substitute in order to facilitate the administrative process. Keywords: Authority, Notary Public, Notary Substitute, Notary Protocol, UUJN ABSTRAKNotaris adalah pejabat umum yang berwenang untuk membuat akta autentik dan memiliki kewenangan lainnya sebagaimana dimaksud dalam Undang-Undang ini atau berdasarkan undang-undang lainnya. Notaris Pengganti merupakan seorang yang untuk sementara diangkat sebagai Notaris untuk menggantikan Notaris yang sedang cuti, sakit, atau untuk sementara berhalangan menjalankan jabatannya sebagai Notaris utama sebagaimana yang dimaksud dalam UUJN. Untuk menjadi Notaris pengganti diharuskan memenuhi syarat tata cara pengangkatan yang sudah di tentukan dalam UUJN maupun dalam Peraturan Menkumham Republik Indonesia. Permasalahannya adalah terdapat perbedaan syarat tata cara pengangkatan antara Notaris dan Notaris pengganti. Notaris pengganti memiliki kewenangan yang hampir sama dengan Notaris. Dalam menjalankan tugasnya sebagai Notaris dan Notaris Pengganti, perlu diketahui kewenangannya agar tidak terjadi penyalahgunaan wewenang. Penulisan jurnal ini bertujuan untuk mengetahui dan menganalisa perbedaan kewenangan dan syarat tata cara pengangkatan antara Notaris dan Notaris pengganti. Dalam upaya mengetahui perbedaan kewenangan antara Notaris dan Notaris Pengganti, penulis menggunakan teori kewenangan dengan metode literatur kaji pustaka terhadap buku-buku yang berkaitan dengan tema jurnal yang saya buat dan bersumber dari beberapa jurnal dari internet. Pentingnya mengetahui perbedaan wewenang antara Notaris dan Notaris pengganti supaya tidak terjadi penyalahgunaan wewenang. Pentingnya mengetahui syarat tata cara pengangkatan antara Notaris dan Notaris pengganti supaya mempermudah proses administrasi.Kata kunci: Kewenangan, Notaris, Notaris pengganti, Protokol Notaris, UUJN